Rethinking the Social : Sociology of Crisis Experience in Central and Eastern Europe - Gadowska, Kaja,; Giza, Anna, (Social Sciences E-Books Online, Collection 2025., 2025)
The book casts a spotlight on Central and Eastern European societies, making their experiences visible and meaningful within the postcolonial discourse. The modernization theory overlooks important aspects of postsocialist transformation. Consequently, sociological knowledge has drifted apart from the social production of knowledge, and sociology has become alarmingly irrelevant to the people it studies. Therefore, the book departs from preconceived notions of "normal" and "modern" to foreground the importance of actual social experience. After all, Central and Eastern Europe is a valuable yet underestimated social laboratory. Thus, the contributors experiment with new theoretical and methodological approaches to bridge the gap between social research and real people. Contributors are: Izabella Bukraba-Rylska, Jacek Burski, Grzegorz Ekiert, Kaja Gadowska, Anna Giza, Małgorzata Głowacka-Grajper, Michał Kaczmarczyk, Krzysztof T. Konecki, Mirosława Marody, Adam Mrozowicki, Joanna Wawrzyniak, Anne White, Renata Włoch, Tomasz Zarycki, and Marek Zirk-Sadowski. See Less